Prospects of introduction of innovative technology overhead passenger traffic on the basis of the passenger ropeways for the modernization of the public transport system of the Bryansk city - Lagerev A.V.; Lagerev I.A. (Научно-технический вестник Брянского государственного университета)
In relation to the current situation in the field of public transport in the Bryansk city was shown the main problems in the implementation of innovative technology for the aerial passenger transport on the basis of suspended passenger ropeways (Cable metro). Shows the advantages of the cable metro-based mechatronic technology transportation compared to the traditional suspended passenger ropeways. Was made the technical and economic feasibility analysis of the construction of the cable metro in conditions of a highly urbanized urban environment of large cities, metropolises and urban agglomerations. Presented the statistical data on the development of vehicles in the Bryansk city in the period 2004-2016 years and based on the analysis of these data shows the feasibility of the development of aerial passenger transport as the most high-speed and environmentally friendly mode of transport compared with automobile and electric transport. Considered the possible sources of financing of design and construction works and shows the commercial attractiveness of the project to potential investors in the framework of public-private partnerships. For existing urban development and major transport flows of the Bryansk city was formulated proposals for the location of future transport cable metro lines, order their gaskets, the formation routes of movement of the rolling stock. Made the estimation of labor and financial costs for the implementation of the project of modernization of the public transport system of the city of Bryansk on the basis of the suspended passenger ropeways. The proposed option has the following characteristics: the number of transport lines - 6, total length - 54.8 km, total number of passenger boarding stations - 26, hub passenger stations – 6, the total number of intermediate supports – 100...110 pieces with a span between supports of 400...600 m. the cost of construction of transport lines and the purchase of necessary passenger and processing equipment will be according to rough estimates of 10.6 billion RUB, cost of building passenger stations – 1.9 billion RUB.